PENGAMATAN INFEKSI JAMUR PATOGEN SERANGGA Metarhizium anisopliae (Metsch. Sorokin) PADA WERENG COKLAT - Y Suryadi; Triny S Kadir (Research Center for Biology-Indonesian Institute of Sciences, 2007)
Observation on infection of fungus entomopathogen Metarhizium anisopliae on insect brown plant hopper was carried out using scanning electron microscope (SEM).The infection of M. anisopliae on insect bodies was shown by conidia sporulation on divergent chain with conidia size of 1.6 x 7.8 urn. Based upon SEM observation, the results revealed that fungus hyphae of M.anisopliae was found on insect body i.e. on cuticle as well as on segment between abdomen, legs and insect facet eyes.In epizootic condition, the cadavers were shown can act as source of fungus dissemination on healthy insect when environment (temperature and humidity) was suitable for primary infection.